Investigating causes of femicide in Egypt: review - Fatma Mohamed Hassan; Maged Nabil Hussein; Asmaa Mohammad Moawad (Egyptian Journal of Forensic Sciences, 2024)
Abstract Background Femicide is a fundamental human rights violation that compromises one’s life, liberty, and personal safety and impedes social and economic advancement. In recent years, Egypt has witnessed an alarming rise in the number of femicide cases. Unfortunately, there is limited data about the magnitude of this problem or factors contributing to the surge in femicide incidents. Consequently, this review aims to discuss the phenomenon of femicide in Egypt, provide an analysis of its causes, and propose possible solutions. Main body Gender disparity, cultural and social norms, impunity, poverty, poor educational level, and insufficient aid services could be contributing factors to femicide in Egypt. Conclusion Identifying the potential causes of femicide in Egypt is essential to prevent and reduce its incidence. So, comprehensive studies to understand the true scope of the problem and to monitor femicide trends in Egyptian society are highly recommended. Policymakers in Egypt should take actual steps to develop an effective action plan to combat femicide.